2013
DOI: 10.1166/jnn.2013.8121
|View full text |Cite
|
Sign up to set email alerts
|

A New Incorporation Method of Metallic Precursors Into a Nafion Film via a Drying Process for thePreparation of Metallic Nanocatalysts/Nafion

Abstract: A new simple drying process was developed in order to prepare a metallic nanocatalysts/Nafion for self-humidifying membrane in a proton-exchange membrane fuel cell (PEMFC). Metallic precursors such as platinum(ll) bis(acetylacetonate) or palladium(ll) bis(acetylacetonate) was sublimed and simultaneously penetrated into the surface of a Nafion film. And then it was reduced to Pt or Pd nanoparticles beneath the film surface without a special reducing agent in a glass reactor of N2 atmosphere at 180 degrees C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In our previous works, we found that ZnO and Ni-P alloy were site-selectively deposited on palladium (Pd) loaded or platinum (Pt) loaded polymer thin film [6][7][8], and we also found that palladium(II) bis(acetylacetonate), Pd(acac)2 and platinum(II) bis(acetylacetonate), Pt(acac)2 were sublimed at 180 o C in vacuum condition and the Pt(acac)2 vapors penetrated into polymer film and spontaneously reduced forming metallic (Pd and Pt) nanoparticles [9,10]. Therefore we could develop a new method to prepare micro-sized Ni-P alloy tube via using a polyacrylonitrile (PAN) fiber with μm sized diameter as a template.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our previous works, we found that ZnO and Ni-P alloy were site-selectively deposited on palladium (Pd) loaded or platinum (Pt) loaded polymer thin film [6][7][8], and we also found that palladium(II) bis(acetylacetonate), Pd(acac)2 and platinum(II) bis(acetylacetonate), Pt(acac)2 were sublimed at 180 o C in vacuum condition and the Pt(acac)2 vapors penetrated into polymer film and spontaneously reduced forming metallic (Pd and Pt) nanoparticles [9,10]. Therefore we could develop a new method to prepare micro-sized Ni-P alloy tube via using a polyacrylonitrile (PAN) fiber with μm sized diameter as a template.…”
Section: Introductionmentioning
confidence: 76%
“…Almost all Pd nanoparticles were loaded on the surface area of the PAN fiber so that the Pd nanoparticles could be acted as seeds for the growth of Ni-P alloy. Pd generation mechanism in a polymer matrix has divided into two steps [10]. That is, the mechanism was composed of (1) nucleation step and (2) growth step in a polymer matrix.…”
Section: Methodsmentioning
confidence: 99%